Die karitiven Formen des Waldenzischen - Siegl, Florian (Helsingin yliopiston kirjasto, 2022)
Forest Enets has two caritive derivations (Sorokina 2010: 148–150; Siegl 2013: 170–172) which, so far, were covered comparatively shallowly. The central task of this study is to delimit the morphosyntax of the verbal -ši and the nominal caritive -šuđ derivations with a short note on functionally and etymologically similar categories in Tundra Enets and Tundra Nenets. Furthermore, the morphosyntactic properties of the Forest Enets nominal caritive will be discussed with special reference to other participant-oriented adjuncts (Himmelmann & Schultze-Berndt 2005) such as essive, benefactive and comitative derivations.